KEMISKINAN DALAM PERSPEKTIF SOSIOLOGI HUKUM : ANALISIS STRUKTURAL, KETIMPANGAN SOSIAL, DAN EFEKTIVITAS KEBIJAKAN HUKUM DI INDONESIA - Raden D.M. Lahanjono; Upik Mutiara; Elia Djalung; Sudarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Poverty is a multidimensional social problem that is not only related to low income levels but also concerns limited access to law, education, healthcare, employment, and social justice. This study aims to analyze poverty from the perspective of sociology of law through structural approaches and the effectiveness of legal policies in Indonesia. The research method used is normative legal research with a sociological approach through literature studies from books, journals, legislation, and national mass media. The results indicate that poverty in Indonesia is influenced by structural social inequality, weak access of poor communities to legal protection, and the dominance of economic policies that are not fully oriented toward social justice. In practice, law has often failed to become an instrument for empowering poor communities and instead tends to reinforce social inequality. Therefore, progressive, humane, and socially just legal reforms are required in accordance with Article 33 of the 1945 Constitution. This study concludes that poverty alleviation cannot rely solely on economic approaches but must involve integration between social, political, and legal policies that prioritize vulnerable communities.